Availability modeling for multi-tier cloud environment. Issue 3 (3rd July 2017) - Nalinipriya, G.; Maheswari, K. G.; Balusamy, Balamurugan; Kotteswari, K.; Kumar Sangaiah, Arun
Abstract: Performance modeling forms an essential process for evaluation of cloud quality. Cloud performance appraisal process and methods widely differ from that of other proven performance related methodologies being used for domains like computer networks, distributed computing and operations systems. Multi-tier Cloud is a scalable system in which many services or tiers can be constructed for all types of applications. The quality of service of a Multi-tier cloud environment is closely associated with several factors like dependability, availability, reliability, security, perform-ability and each of the performance entities directly or indirectly influences the overall functioning of the cloud. There are many models to evaluate cloud performance and quality, but these traditional models are not efficient enough and consider only certain primary parameters in their evaluation. In this paper, a high-level performance analysis model is proposed that can predict the availability of a Multi-tier cloud environment. As Multi-tier cloud deals with multiple services according to their application, the prediction of availability is essential one for performance modeling. The various prominent parameters that influence the performance of the cloud system are also considered in the proposed model. The proposed algorithm is experimentally verified by means of SHARPE tool.